Effect of Loading Rate on Tensile Strength and Fracture Stress of Chocolate - Nedomová, Šárka; Kumbár, Vojtěch; Trnka, Jan; Šafránková, Veronika; Dufková, Renáta; Votava, Jiří; Hřivna, Luděk; Buchar, Jaroslav (Wiley-Blackwell, 2025)
The fracture properties of five types of chocolate (dark, extra dark, milk, white, and ruby) were investigated using an indirect tensile test known as the Brazilian test. Two different loading rates of 0.0017 m/s and around 12 m/s were used through the universal testing machine TIRATEST and split Hopkinson pressure bar (SHPB) technique. Results show that the tensile fracture stress increases with the loading rate. The sensitivity of the fracture stress at low-loading rates is lower than that at the high-loading rates. The obtained results can be used in industry for the correct processing of chocolate products and their transport. The presented methods can be also used to detect defects in chocolate products.
Keywords: Brazilian test; chocolate; fracture properties; loading rate; split Hopkinson pressure bar; tensile strength